(untitled) (Research, Society and Development, 2020)
The internationalization of education proves to be an innovative and complex strategy that can respond to educational needs in a scenario in which the globalized society and the challenges of the world of work are articulated. Educational policies and education systems in different countries have sought to improve on this scenario. This paper aims to demonstrate how a public institution of Vocational and Technological Education (EPT) in Brazil, the Paula Souza Center, has been building its internationalization actions in order to make its students better prepared for contemporary requirements. The research is qualitative, based on bibliographic and documentary research, that highlight the institutional strategies. Based on the structure of an advisory service linked to the institution’s superintendence, there are actions that promote and make possible projects of approximation with international institutions, with special attention to the project of exchange of professors and students of higher education. It is observed that the Paula Souza Center institutional internationalization project, constantly under construction, proposes methods and processes with a view to improving the quality and and strategic character of Vocational and Technological Education.